ANALISIS KEPUASAN KONSUMEN PENERBANGAN DOMESTIK Pada Maskapai Garuda Indonesia - Achmad Akbar Rivai (2020)
This research is using quantitative study aimed to see whether there are influence of brand image, and service quality on customer satisfaction. This study uses Garuda Indonesia airline customers as many as 50 respondents as a sample. The sample selection is done based on established criteria. This study uses descriptive analysis with index scale and testing the hypothesis in this study was used the Individual Statistical Test with the SmartPLS 3.2 program and the significance level of 5% (0.05). The results of testing are obtained (1) there is an influence of brand image on customer satisfaction, (2) there is no influence of service quality on customer satisfaction. That's because some of the respondents in this research are Garuda Miles members who have often used Garuda Indonesia and have trusted the Garuda Indonesia brand so that service quality is not a determining factor of satisfaction.